Pengetahuan dan perilaku masyarakat terhadap keberadaan jentik nyamuk Aedes aegypti : Vektor penyakit demam berdarah dengue - Devita Febriani Putri; Tusy Triwahyuni; Jovita Mutiara Saragih (Holistik Jurnal Kesehatan, 2021)
Community knowledge and behavior towards Aedes aegypti larvae presence : Vector of dengue hemorrhagic feverBackground: Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus which is transmitted through mosquitoes, especially Aedes aegypti and Aedes albopictus. alternative vector control strategies are needed to prevent the spread of DHF. Public understanding of the existence of DHF vectors including Aedes aegypti mosquito larvae and behavior how to handle them has a significant influence in the control of DHF vectors.Purpose: Knowing correlation between community Knowledge and Behavior towards aedes aegypti larvae Presence : Vector of dengue hemorrhagic feverMethod: Quantitative analytic research with cross-sectional approach. A sample of 95 respondents and taken by simple random sampling and carried out at Way Kandis village-Bandar Lampung. Interview respondents with a questionnaire and home observation using the observation sheet.Results: Chi-square analysis shows that there is a significant association between community knowledge and behavior towards aedes aegypti larvae presence: Vector of dengue hemorrhagic fever with a p-value of 0.004 and  p-value of 0.023.Conclusion: There is a significant association between community knowledge and behavior towards aedes aegypti larvae presence: Vector of dengue hemorrhagic fever. The community at Way Kandis village-Bandar Lampung need more educated regarding aedes aegypti larvae follow up by local health authority.Keywords: Community knowledge; Behavior towards; Aedes aegypti larvae; Dengue hemorrhagic feverPendahuluan: Demam Berdarah Dengue (DBD) merupakan penyakit yang disebabkan oleh virus dengue yang ditularkan melalui nyamuk terutama Aedes aegypti dan Aedes albopictus. Strategi pengendalian melalui vektor merupakan alternatif yang diperlukan untuk mencegah penyebaran penyakit DBD. Pemahaman masyarakat tentang keberadaan vektor DBD diantaranya jentik nyamuk Aedes aegypti dan perilaku cara menanganinya memberikan pengaruh signifikan dalam pengendalian vektor DBD.Tujuan: Mengetahui hubungan pengetahuan dan perilaku masyarakat dengan keberadaan jentik nyamuk Aedes aegypti di Kelurahan Way Kandis.Metode: Penelitian analitik dengan pendekatan cross sectional. Tehnik sampling menggunakan simple random sampling, dengan jumlah sampel 95 responden. Pengambilan sampel dengan wawancara menggunakan kuesioner serta melakukan observasi rumah responden dengan menggunakan lembar observasi.Hasil: Analisis Chi-square menunjukan, terdapat hubungan bermakna tingkat pengetahuan masyarakat Way kandis terhadap keberadaan jentik nyamuk Aedes aegypti dengan p-value sebesar 0,004 dan terdapat hubungan bermakna perilaku masyarakat Way kandis terhadap keberadaan jentik jentik nyamuk Aedes aegypti  dengan p-value sebesar 0,023.Simpulan: Ada hubungan yang signifikan antara pengetahuan dan perilaku masyarakat terhadap keberadaan jentik aedes aegypti. Masyarakat di Desa Way Kandis-Bandar Lampung perlu lebih diedukasi terkait jentik aedes aegypti yang ditindaklanjuti oleh dinas kesehatan setempat.